Determinants of Audit Quality in Companies That Conduct Initial Public Offerings: Determinan Kualitas Audit Pada Perusahaan Yang Melakukan Initial Public Offering - Tania, Dinda; Tarmizi , M. Irfan; Adrian , Muhammad (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to investigate factors that affect quality control, including audit period, auditor reputation, accounting firm size, and audit fees. The population of this study consisted of 54 companies that participated in the Initial Public Offering (IPO) and were listed on the Indonesia Stock Exchange (IDX) in 2021. The sample was taken using the purposive sampling method to obtain a sample of 42 companies. This study uses quantitative data analysis techniques. SPSS version 20 is used for statistical analysis in data analysis. From the results of this study, audit tenure, Public Accounting Firm size, and audit fees do not affect audit quality; partial research confirms that auditor reputation significantly impacts audit quality. The results of this study can be used as a reference for auditors to improve audit quality for companies conducting IPO.